Pengaruh Literasi Membaca terhadap Pembelajaran IPS pada Mahasiswa PGSD Universitas Muhammadiyah Sorong: Pengaruh Literasi Membaca terhadap Pembelajaran IPS pada Mahasiswa PGSD Universitas Muhammadiyah Sorong - Irfandi Idris; Rizky Ekawaty Ahmad; Ramin Ode; Umar; Nisya Dian Anggraini (UNIB Press, 2023)
This study aims to assess the reading literacy skills of PGSD students at Muhammadiyah University of Sorong. Low reading proficiency adversely impacts learning outcomes, particularly in the field of social studies education. The students' low reading proficiency leads to a lack of comprehension of the reading material. Therefore, to improve the development of students' competencies and interest in reading culture The research methodology employed is quantitative, with a sample of 100 PGSD students at Muhammadiyah University of Sorong. Data analysis was carried out using simple linear regression. This is evident from the results of the simple linear regression test, which yielded a significant value of 0.00, less than the set significance level of α = 0.05. The findings of this study indicate that reading literacy significantly influences the reading interest of PGSD students. The research results reveal the following: (1) 67.53% of students exhibit adequate reading literacy skills, (2) 81% of students achieve very good learning outcomes, and (3) there is a noteworthy 5.4% correlation between reading literacy skills and student learning achievement.